Relationship Between ChatGPT Use and EFL Students’ Perceived Usefulness, Ease, Dependence, And Creativity - Dzimar, Muhammad; Maulida, Nindya Rahma; Jannah, Lia Roudlotul; Rahmah, Rayinda Eva (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
AI tools like ChatGPT are changing the way we teach and learn English as a foreign language. They make it easier for students to get quick feedback, generate fresh ideas, and dive into fun, creative writing exercises. However, here's the catch: if students lean too heavily on these tools, they might start losing their own sense of independence in learning. This research investigates how the frequency of ChatGPT use relates to EFL students’ perceptions of its usefulness, ease of use, dependence, and its role in fostering creativity in learning English. Adopting a quantitative correlational design with an ex post facto approach, the study involved 38 fifth-semester students from an English Education Department at a university in Pekalongan. Data were gathered through a Likert-scale questionnaire and analyzed using Spearman’s Rank Correlation. Our findings revealed strong positive relationships between how often students use ChatGPT and their perceptions of its usefulness, ease of use, dependence, and creativity. The tightest link was with usefulness (r = 0.811, p < 0.05), followed by creativity (r = 0.658), dependence (r = 0.640), and ease of use (r = 0.584). In short, the more students interact with ChatGPT regularly, the more they value it as a practical and user-friendly learning aid; however, this also increases their reliance on AI for help. The study highlights the importance of pedagogical approaches that foster critical awareness and autonomous learning when integrating ChatGPT into language education